Kawin Hamil di Luar Nikah - Rahim, Syahbudi (Tasamuh: Jurnal Studi Islam, 2017)
In the perspective of Sadd al-dzari’ah motivated by the opportunity mafsadat contained in Article 53 KHI. The mafsadat opportunities is the lack of clarity limits because the pregnancy is allowed to do married pregnant in Article 53 KHI. The impact, it is not uncommon Article 53 KHI used as mating legality pregnant pregnancy due to adultery. This is clearly not in accordance with Islamic law strictly prohibits the practice of adultery. To analyze these problems, so in this study the two proposed formulation of the problem, namely, how Article 53 KHI in perspective sadd al-dzari’at and how the formulation of Article 53 KHI as a solution marries pregnant. This study is a qualitative research, in which the data were collected by library method. While the process is done, it is analyzed by descriptive and qualitative analysis method. Based on the results obtained, it can be seen that the existence of Article 53 KHI is a means to protect human rights, but contained mafsadat aspects related to the implementation of sharia law on any sexual act outside of marriage. To eliminate aspects of mafsadat in Article 53 KHI, in the context of saddu al-dzari’at, it is necessary to change editorial form of additional provisions limiting the causes of pregnancy and accompanying sanctions. Formulation of Article 53 KHI as pregnant mating solutions can be realized by adding editorial restrictions associated with mating because pregnant can be implemented without any penalties and sanctions for pregnant mating caused adultery social form of repentance